Voices of Young Readers: A Phenomenological Study of Grade 2 Pupils’ Experiences with the Google Read Along App - Nancy T. Rubin; Arnel S. Travero; Angelie T. Padilla (Research Synergy Foundation Press, 2026)
In the digital age, mobile-assisted learning tools are increasingly being used to address early literacy challenges among young learners, particularly in resource-constrained educational settings. This phenomenological study explored the lived experiences of Grade 2 pupils who engaged with the Google Read Along application as part of a classroom-based reading intervention. Conducted at a public elementary school in the Division of Cagayan de Oro City, the Philippines, the research aimed to understand how young learners perceived and responded to a mobile-assisted reading tool designed to enhance reading comprehension and vocabulary. Through informal interviews and thematic analysis, three (3) key themes emerged: increased enjoyment of reading, vocabulary development and learning gains, and motivation through positive reinforcement. The findings revealed that pupils experienced reading as more engaging and meaningful due to the app’s interactive features, gamified rewards, and supportive feedback. These experiences contributed not only to cognitive gains in vocabulary but also to affective growth in reading motivation and confidence. The study affirms the potential of mobile-assisted learning tools in foundational literacy instruction, especially when thoughtfully integrated into learner-centered classroom environments. Implications are offered for educators, developers, and policymakers seeking to improve early-grade reading outcomes through technology.